2022
DOI: 10.1002/adhm.202200960
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Recruitment and Degradation of Estrogen Receptor α by Photothermal Polydopamine Nanoparticles for Breast Tumor Ablation

Abstract: The major challenges of photothermal therapy (PTT) toward clinical application are the severe skin injury and inflammation response associated with high power laser irradiation. Herein, polydopamine nanoparticles (PDA-EST and PDA-RAL) targeted to estrogen receptor 𝜶 (ER𝜶) for efficient ablation of breast tumor under a low irradiation density of 0.1 W cm -2 are reported. These nanoparticles are capable of recruiting ER𝜶 on their surface and induce a complete ER𝜶 degradation via localized heat. Owing to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The photothermal antibacterial property of HPDA-PB NPs was initially assessed by combining PBS dispersion of HPDA-PB NPs with a solution containing S. aureus, resulting in the formation of six dispersions with varying concentrations (20,40,60,80, 100, 200 µg ml −1 ) of HPDA-PB NPs and a fixed concentration (5 × 10 7 cfu) of S. aureus. Each group's volume was adjusted to 300 µl and added to a 96-well plate for incubation at 37 • C for 30 min.…”
Section: In Vitro Antibacterial Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The photothermal antibacterial property of HPDA-PB NPs was initially assessed by combining PBS dispersion of HPDA-PB NPs with a solution containing S. aureus, resulting in the formation of six dispersions with varying concentrations (20,40,60,80, 100, 200 µg ml −1 ) of HPDA-PB NPs and a fixed concentration (5 × 10 7 cfu) of S. aureus. Each group's volume was adjusted to 300 µl and added to a 96-well plate for incubation at 37 • C for 30 min.…”
Section: In Vitro Antibacterial Assaymentioning
confidence: 99%
“…Therefore, the conditions for the enzymatic activities of PB can vary depending on the specific experimental setup and modifications applied to the PB NPs [18]. Polydopamine NPs (PDA NPs), a melanin-like biomimetic material [19], have found extensive applications in antibacterial [20][21][22] and antitumor studies [23,24] owning to their remarkable photothermal ability [20] and excellent biosafety [25]. It is worth noting that although several PDA based photothermal materials have been well documented, their low optical energy harvesting efficiency in both aqueous and solid states hinders their application in this field.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the heterogeneous structure and abnormal vascular distribution in tumors, the low targeting and low penetration of nanomaterials greatly affects the uniformity of heat generated by ICG-mediated PTT, ultimately leading to tumor metastasis and recurrence. 6,29 To address this limitation, a photothermal nanocluster (ICG@HSA-Azo-HP) was constructed by loading ICG onto human serum albumin (HSA), subsequently crosslinking it with a thermoresponsive azo linker (VA057), and modifying the specic homing/penetrating tLyP-1 peptide (HP). 30 The nanoclusters (149 nm) were selectively aggregated at the tumor site by the EPR effect and then decomposed into small particles (11 nm) with enhanced intratumor diffusion ability under 808 nm laser irradiation.…”
Section: Cyanine-based Nanomaterialsmentioning
confidence: 99%
“…According to the recent statistics of the International Agency for Research on Cancer, breast cancer has become the most diagnosed cancer in both sexes [87]. Much attention has been paid to develop novel materials for breast cancer treatment [88][89][90][91]. Recently, increasing number of studies have shown the efficiency of single-atom nanozymes in breast cancer therapy.…”
Section: Breast Cancer Treatmentmentioning
confidence: 99%